2023
DOI: 10.3390/plants12020256
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Physiological and Biochemical Responses of Field Pea Genotypes under Terminal Heat Stress

Abstract: Field pea is one of the important short-duration cool season pulse crops which contributes significantly towards food and nutritional security. Two heat-susceptible (HS) and two heat-tolerant (HT) genotypes were selected from the previous study for further characterization. A significant variation was observed for morpho-physiological traits studied. Principal component analysis explained that first two principal components, i.e., PC1 and PC2 showed 76.5% of the total variance in optimal condition, whereas 91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…It indicates that they may play a very important role in mitigating the prevailing stress by balancing their level in the cell. Similar results were observed by Sharma et al [ 94 ], Anee et al [ 3 ], Hasanuzzaman and Fujita [ 95 ], Nakano and Asada [ 55 ], Hasanuzzaman et al [ 96 ], Lin et al [ 97 ], and May et al [ 98 ] in sesame and other crops for different stresses.…”
Section: Discussionsupporting
confidence: 86%
“…It indicates that they may play a very important role in mitigating the prevailing stress by balancing their level in the cell. Similar results were observed by Sharma et al [ 94 ], Anee et al [ 3 ], Hasanuzzaman and Fujita [ 95 ], Nakano and Asada [ 55 ], Hasanuzzaman et al [ 96 ], Lin et al [ 97 ], and May et al [ 98 ] in sesame and other crops for different stresses.…”
Section: Discussionsupporting
confidence: 86%
“…Salinity induces a marked reduction in the growth of wheat cultivars via the excessive build-up of Na + and Cl − and reducing nutrient uptake and photosynthetic performance [ 64 , 65 , 66 ]. However, the application of Si significantly improved wheat growth and yield under saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a better antioxidant enzyme system, as evidenced by the higher activities of SOD, POX, and APX in heat-tolerant wheat genotypes, could be an indicator that these genotypes are more efficient at scavenging superoxide anions produced in plants due to heat stress and provides a plausible explanation for their tolerant nature under stress conditions. Overexpression of SOD and APX genes, which are utilized in ROS scavenging, has been reported to be one of the mechanisms of enhanced antioxidative defense and ultimately improved tolerance to abiotic stresses ( Lee et al., 2007 ; Hamurcu et al., 2020 ; Chugh et al., 2022 ; Sharma et al., 2023 ). Rajjou and Debeaujon (2008) suggested that a well-developed detoxification mechanism due to the higher activity of antioxidant enzymes in dry seeds helps to preserve their high germination ability.…”
Section: Discussionmentioning
confidence: 99%